Evaluation of EBV-LMP1 as prognostic indicator of nasopharyngeal carcinoma in Indonesian patients (Faculty of Medicine Universitas Indonesia, 2002)
Forty eight cases of nasopharyngeal carcinoma patients who had been treated with radiotherapy were analysed for the expression of EBER in the nucleus of the tumor cells by in situ hybridization technique. EBER was expressed in 69% of the cases. Histologic specimens positive for EBER were then examined for the expression of EBV-LMP1 by immunohistochemistry, which showed 68% positivity. Clinical staging of 48 cases and radiation response of 32 cases were collected. Data of up to 2 years of survival of 16 cases were obtained through postal and phone communication. Statistical analysis showed that the Working Formulation histologic classification of NPC correlated significantly with radiation response. The expression of EBV-LMP1 was correlated significantly with the survival of the patients. Thus EBV-LMP1 which has been shown to possess influence on lymphoid and epithelial cells, clinicopathologically proved to have a function as prognostic indicator. (Med J Indones 2002; 11: 81-6)Keywords: nasopharyngeal carcinoma, histopathologic types, EBER, EBV- lmp1, survival